Educational Accountability through the Lens of Elementary School Teachers in Public Sector - Fatima, Kiran; Abiodullah, Muhammad (Journal of Applied Research and Multidisciplinary Studies, 2022)
This study was designed to explore teachers’ perception about educational accountability in their job. The main objective of the study was to identify teachers’ perception about educational accountability in their job. This study was based on the job demands-resources models and results from previous studies. Researcher employed a cross-sectional survey research. The sample of this study were 375 elementary school teachers for quantitative data collection drawn from total population of district Lahore and Kasur through Taro Yamane’s formula. Furthermore, 18 participants for qualitative data collection. Proportionate stratified random sampling was used to select sample of 375 respondents from two districts Lahore and Kasur for quantitative data collection. Quantitative data was statistically analyzed through SPSS version 15 by using descriptive statistics (Mean, ranges, and standard deviation). Quantitative findings revealed that teachers’ had positive perception about educational accountability.